2012
DOI: 10.1590/s0036-46652012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Oral colonization by yeasts in HIV-positive patients in Brazil

Abstract: INTRODUCTION: In HIV-infected patients, colonization of the oral cavity by potential pathogenic yeast may lead to development of systemic fungemia. We evaluated the prevalence of yeast in the oral cavity of Brazilian HIV-positive patients and verified whether or not the species characterized were enzymatically active. Furthermore, the species identified were tested for their susceptibility to antifungal treatment. METHODS: Patient saliva and oropharyngeal candidiasis samples were collected from 60 seropositive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
85
3
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 38 publications
21
85
3
15
Order By: Relevance
“…However, the epidemiology of yeast infection is rapidly evolving, and non-albicans Candida species have emerged as major opportunistic pathogens primarily in the specific conditions of immunodeficiency, such as acquired immunodeficiency syndrome. 12 The present results showed that most Candida species (92%) produced hemolysins; of these species, 58% had strongly positive hemolytic activity. These findings agree with those of Ramesh et al 17 who compared the hemolytic activity of 50 Candida strains isolated from patients with HIV and 10 Candida strains isolated from immunocompetent patients.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, the epidemiology of yeast infection is rapidly evolving, and non-albicans Candida species have emerged as major opportunistic pathogens primarily in the specific conditions of immunodeficiency, such as acquired immunodeficiency syndrome. 12 The present results showed that most Candida species (92%) produced hemolysins; of these species, 58% had strongly positive hemolytic activity. These findings agree with those of Ramesh et al 17 who compared the hemolytic activity of 50 Candida strains isolated from patients with HIV and 10 Candida strains isolated from immunocompetent patients.…”
Section: Discussionsupporting
confidence: 46%
“…The strains were isolated and identified as previously described by Junqueira et al 12 The isolates tested included the following species:…”
Section: Candida Strainsmentioning
confidence: 99%
“…The dominant species reported in previous studies of the mucous membrane was Candida albicans, isolated from 60-89% of subjects [17,18,[22][23][24]. Other species were recorded with significantly lower incidence: C. parapsilosis in 33% and C. tropicalis only in 13% of patients [2,3,20,21,[25][26][27].…”
Section: Discussionmentioning
confidence: 95%
“…O aumento da incidência das infecções fúngicas tem sido associada a pacientes com comprometimento do sistema imunológico 1,2,3 , Candida albicans é a espécie frequentemente isolada 4,5,2,3 . No entanto, outras espécies têm aumentado significativamente sua prevalência, dentre estas C. tropicalis 6,3,7 .…”
Section: Introductionunclassified